Current approaches for assisted oocyte maturation in camels - Islam M. Saadeldin; Jongki Cho (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Camel (camelus dromedarius) is a unique large mammalian species that can survive harsh environmental conditions and produce milk, meat, and wool. Camel reproduction is inferior when compared to other farm animal species such as cattle and sheep. Several trials have been reported to increase camel reproduction and production through assisted reproductive techniques (ARTs) such as in vitro fertilization and cloning. For these reasons, obtaining enough mature oocytes is a cornerstone for ARTs. This demand would be improved by the oocyte in vitro maturation (IVM) systems. In this review, the current approaches and views from different laboratories using ARTs and the IVM to produce embryos in vitro in camel species. For the last two decades, conventional IVM system was the common approach, however, recently the bi-phasic IVM system has been introduced and showed promising improvement in IVM of camel oocytes. Detailed studies are needed to understand camel meiosis and IVM to efficiently increase the production of this species.